2015
DOI: 10.3389/fpsyg.2015.00161
|View full text |Cite|
|
Sign up to set email alerts
|

Tactile input and empathy modulate the perception of ambiguous biological motion

Abstract: Evidence has shown that task-irrelevant auditory cues can bias perceptual decisions regarding directional information associated with biological motion, as indicated in perceptual tasks using point-light walkers (PLWs) (Brooks et al., 2007). In the current study, we extended the investigation of cross-modal influences to the tactile domain by asking how tactile input resolves perceptual ambiguity in visual apparent motion, and how empathy plays a role in this cross-modal interaction. In Experiment 1, we simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…In temporal ventriloquism effect, the perceived time onsets/time intervals of target eventsvisual events (with lower temporal resolutions) could usually be biased with the presence of the distractorsauditory stimuli or tactile events (with higher temporal resolutions) when all the events are within the presumed temporal window [14] . By exploiting the temporal ventriloquism effect, we have implemented empirical psychophysical studies to show that the ambiguous percept of visual apparent motion could be resolved with the well-designed (alignments) of auditory inputs [15][16][17][18] and tactile inputs [19,20] . In telepresence, we showed that synchronous perception of cross-modal (visuo-haptic) events was very sensitive to the visual packet loss rate.…”
Section: Temporal Ventriloquism and Perceptual Organizationmentioning
confidence: 99%
“…In temporal ventriloquism effect, the perceived time onsets/time intervals of target eventsvisual events (with lower temporal resolutions) could usually be biased with the presence of the distractorsauditory stimuli or tactile events (with higher temporal resolutions) when all the events are within the presumed temporal window [14] . By exploiting the temporal ventriloquism effect, we have implemented empirical psychophysical studies to show that the ambiguous percept of visual apparent motion could be resolved with the well-designed (alignments) of auditory inputs [15][16][17][18] and tactile inputs [19,20] . In telepresence, we showed that synchronous perception of cross-modal (visuo-haptic) events was very sensitive to the visual packet loss rate.…”
Section: Temporal Ventriloquism and Perceptual Organizationmentioning
confidence: 99%